Optimal Monetary Policy in a Small Open Economy with Habit Formation and Nominal Rigidities - Jung, Yongseung (IMF Working Papers; Working Paper, 2003)
Introducing habit formation into an open economy macroeconomic model with price stickiness, we examine the characteristics of an optimal monetary policy. We find that, first, the optimal policy rule entails interest rate smoothing and responds to the lagged values of the foreign interest rate and domestic technology shocks as well as their current values. Second, habit formation enriches the dynamics of the economy with a persistent, hump-shaped response of consumption to shocks. Finally, when habit formation does matter, the optimal policy rule achieves a greater welfare improvement over alternative policy rules by achieving lower macroeconomic variability.